Quantum Dimension and Quantum Projective Spaces - Matassa, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We show that the family of spectral triples for quantum projective spaces introduced by D'Andrea and Dąbrowski, which have spectral dimension equal to zero, can be reconsidered as modular spectral triples by taking into account the action of the element K₂ρ or its inverse. The spectral dimension computed in this sense coincides with the dimension of the classical projective spaces. The connection with the well known notion of quantum dimension of quantum group theory is pointed out.